Toxoplasma gondii infection modulate systemic allergic immune response in BALB/c mice - Fenoy, Ignacio Martín (2015)
The increased prevalence of allergies in developed countries has been attributed to a reduced exposure to some microbes. In agreement with epidemiological studies, we previously showed that Toxoplasma gondii infection prevents allergic airway inflammation. The mechanisms would be related to the strong Th1 response induced by the parasite and to regulatory cell induction. Herein we further characterized whether T. gondii allergy modulation extents to a systemic level or if it is limited to the lung. Parasite infection before allergic sensitization resulted in a diminished Th2 cytokine response and, when sensitized during acute infection, an increased in TGF-β production was detected. Allergen specific T cell proliferation was also reduced. Sensitization during both acute and chronic phases of infection resulted in a decreased anaphylaxis reaction. Our results extend earlier work and show that, in addition to lung airway inflammation, T. gondii infection can suppress allergic responses at systemic level. These results open the possibility that this protozoan infection could modulate other allergic disorders such as atopic dermatitis or oral allergies. Understanding the mechanisms by which different microorganisms regulate inflammation may potentially lead to the development of strategies aimed to control atopic diseases.